2008
DOI: 10.1097/rlu.0b013e318177934e
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG Uptake in Cutaneous Metastases From Breast Cancer

Abstract: Cutaneous metastases from internal malignancies are rare with a reported incidence between 0.7% and 10%. Among all malignancies the highest incidence of cutaneous metastasis is seen in breast cancer. We report the detection of distant dermal metastases from breast cancer on F-18 FDG PET imaging. A 73-year-old woman with metastatic left breast cancer was referred for F-18 FDG PET/CT scan, which showed multiple FDG avid lesions along cutaneous and subcutaneous nodules in the posterior neck, bilateral proximal ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…A similar identification of 40% primary tumors was demonstrated with PET/computed tomography (CT) but with the concurrent advantage of less incorrect positive results (101). On the contrary, PET examinations in the staging of internal metastases yield the detection of cutaneous metastases (135).…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…A similar identification of 40% primary tumors was demonstrated with PET/computed tomography (CT) but with the concurrent advantage of less incorrect positive results (101). On the contrary, PET examinations in the staging of internal metastases yield the detection of cutaneous metastases (135).…”
Section: Diagnostic Approachmentioning
confidence: 99%
“…In 2008 Borkar S et al (28) reported another case of distant cutaneous metastasis from ductal carcinoma left breast in a 73 year old female which was detected in 18F-FDG PET SCAN. SHELKE VN et al in 2012 reported a case of multiple distant cutaneous metastasis from ductal carcinoma of breast in a 47 year old male patient.…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous metastasis is an unusual site. It can occur either via lymphatic or hematogenous spread, and is commonly seen in the head and neck regions, as well as the trunk and extremities (3,5,9,10). The most common site of metastasis is reported as the chest, which was involved in 28.4% of metastatic lesions (3,11).…”
Section: Literature Review and Discussionmentioning
confidence: 99%
“…It has higher sensitivity than other conventional methods in terms of detecting skin and soft tissue metastasis. It has a significant impact on the choice of treatment and management (8,10).…”
Section: Literature Review and Discussionmentioning
confidence: 99%